The Exchange Rate Regime: Which Institutions to Strengthen the Viability of Corner Solutions? Array - Sali, Alhadj Malloum; Abessolo, Yves André; Dazoue, Dongue Guy Paulin (EuroEconomica, 2020)
Abstract : The purpose of this work is to examine the sustainability of bipolar exchange rate regimes, taking into account the role played by the quality of institutions. The study is based on data from 134 IMF member countries over the period 1984-2013. The results of the econometric estimates obtained with the method show that, using the classification of Reinhart and Rogoff (2016), we have three types of conclusions depending on the type of financial crisis studied. Thus, for banking crises, the sustainability of floating exchange rate regimes is higher than that of fixed regimes. This sustainability increases for countries with fixed exchange rate regimes with government stability and for countries with floating regimes with an improved business climate, the fight against corruption and a relatively low presence of the military in politics. For exchange rate crises, we find a superiority of fixed regimes in terms of sustainability compared to flexible regimes. This is increasing in both exchange rate regimes, with less involvement of the military and religion in politics and the strengthening of the rule of law. Finally, with regard to debt crises, we have a superior sustainability of fixed regimes thanks to institutions such as: the quality of bureaucracy, the business climate, socio-economic conditions and government stability.